Prepontine Chordoma Presenting with MRI Features of an Epidermoid Cyst: Case Presentation and a Mini-Review - Ozek, Erdinc; Bolukbasi, Fatih H.; Baskan, Ozdil; Altinoz, Meric A.; Sav, Aydin; Elmaci, Ilhan (Current Medical Imaging, 2018)
Background: We report a patient with a prepontine chordoma, presented with MRI features of an Epidermoid Cyst (EC) including hypointensity on T1-weighted image, hyperintensity on T2- weighted image, hyperintensity on DWI, and no contrast enhancement. We also presented a concise review of the relevant clinical data, since such cases were rarely reported in the English medical literature. Results & Conclulsion: To avoid delays in the management of patients with this locally aggressive tumor, clival chordoma should be taken into consideration as a differential diagnosis of tumors residing in close proximity to the clivus even in the absence of a bony erosion.
Keywords: epidermoid cyst